Traditional futures law and custom in India's Lakshadweep Islands - Vijaya Kumar, V. (Oxford Univ. Press, 2006)
Under the customary matrilineal law of succession evolved in the islands and followed for centuries, joint family property devolves from mothers to daughters. After marriage women continue to live with their maternal joint family, as do their children
Includes bibliographical references (p. [311]-318) and indexes
Keywords: Customary law -- India -- Lakshadweep; Inheritance and succession -- India -- Lakshadweep; Matrilineal kinship -- India -- Lakshadweep; Rechtssystem; Indien; Lakkadiven